THE PEDAGOGICAL SIGNIFICANCE OF SMART TECHNOLOGIES IN TRAINING FUTURE PRIMARY SCHOOL TEACHERS (International conference on multidisciplinary science, 2025)
This article examines the pedagogical importance of Smart technologies in preparing future primary school teachers. It explores how digital tools improve professional competence, enhance instructional design skills, foster interactive learning, and strengthen educators’ readiness for 21st-century classroom demands. The paper highlights neuroscientific, methodological, and pedagogical perspectives on Smart integration within teacher education.